Studi Deskriptif Sikap Peduli Siswa Terhadap Kesenian Daerah Bengkulu - Keken Veratianty; Puspa Djuwita; Resnani Resnani (JURIDIKDAS, 2019)
The purpose of this study was to describe the caring attitude of students towards Bengkulu regional arts. The focus of this research is on one of the Bengkulu regional arts namely Bengkulu regional song. This type of research is qualitative, the research method used is descriptive qualitative. The subjects of the study were students and teachers of VB grade SDN 68 Bengkulu City. The research instrument was the researcher himself using observation guidelines and interview guidelines. Data collection techniques used were observation, interviews, and documentation. Data analysis technique is done by examining all data obtained from observations and interviews that have been recorded and the results of documentation, data that has been obtained are analyzed through data reduction, data presentation, and drawing conclusions. Data credibility testing is done through increasing perseverance and triangulation. The results of this study are students' caring attitude towards Bengkulu regional art in the VB class SDN 68 Bengkulu City already seen. The caring attitude of students towards Bengkulu regional arts in the VB class SDN 68 Bengkulu City has fulfilled almost every descriptor of the three indicators of caring attitude towards regional arts.